EVALUASI PROGRAM PEMBINAAN, PELATIHAN GELANDANGAN DAN PENGEMIS - Reza Aprina, Febri Yuliani, Zaili Rusli (Universitas Riau, 2019)
Development Program Evaluation, Vagrant Training and Beggars. The purpose of this study was to determine the evaluation of homeless and beggar training training programs in Pekanbaru City as well as what factors influence the evaluation of homeless and beggar training training programs in Pekanbaru City. This study uses approach, observation and documentation. Qualitative descriptive research method. Primary data is obtained directly through interviews, research informants namely the Head of Social Rehabilitation Division, Head of the Secretariat / Responsible Division of Salter, Salter employees, and the community. Data analysis uses interactive methods ranging from data reduction, data presentation and conclusion drawing. The results of this study indicate that the implementation of the Evalution of the implementation of training programs for homeless and beggar training in the city of Pekanbaru has not yet achieved the expected results, in which the implementation of social welfare goals is sprawl.